WANPRESTASI DALAM PERJANJIAN PINJAMAN PADA CREDIT UNION SADA NIOGA DI DESA GUNUNG MERIAH KABUPATEN DELI SERDANG SUMATERA UTARA - LOPIANTI BR SEMBIRING; Hayatul Ismi; Hengki Firmanda S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The activity of lending and borrowing money has been carried out for a long time in people's lives who recognize money as a means of payment. The lending and borrowing relationship can be made by an agreement between the borrower (debtor) and lender (creditor) as outlined in the form of an agreement. The debt and receivable agreement in the Civil Code can be identified with a loan and borrowing agreement, namely a loan and loan agreement in the form of money on condition that the borrower will replace it with the same amount as when borrowing. Regarding lending and borrowing, it is also stated in Article 1754 of the Civil Code, namely "Lending and Borrowing is an agreement in which one party gives the other party an amount of goods that have been used up, provided that the latter party wants to return the same amount of the same type and quality". In general, the word cooperative comes from the word "Ko" which means together and "operation" which means work, so cooperatives mean working or trying together, the International Cooperative Alliance (ICA) defines cooperatives as follows "Cooperatives are groups of people or body units. whose members jointly help each other by limiting profits and their business must be based on cooperative principles. Credit Union (CU) comes from Latin, namely Crede which means trust and Unio which means association, so it can be interpreted that Credit Union is a movement of associations that trust each other. The Lending Program at CU Sada Nioga itself is also a credit or lending activity that uses low interest. This makes members who are members of the cooperative feel lighter and more confident in increasing their business. Loans made by members will get a loan interest of 2%. However, even though some of these principles have been explained, there are still some members who are negligent in carrying out their obligations. There are eight (8) people who have never made loan installment payments and made negligence as according to R. Subekti, namely "Carrying out what was promised, but not as agreed".Keywords: Default, Loan Agreement, Credit Union